Zinc oxide nanostructures: the effect of deposition parameters on the electrical properties using sol-gel method - Kamaruddin, Sharul Ashikin (2008)
Nanostructured Zinc Oxide (ZnO) has been deposited on Silicon Dioxide (Si02) using sol-gel method. The Si02 was grown on Silicon (Si) using dry oxidation process in 1 atrn ambient. In sol-gel method. a lot of deposition parameters need to be considered to remain the uniformity v and reproducibility. Any small changes in the deposition parameters will affect the surface morphologies, electrical properties and optical properties as well. This research is done to study the deposition parameters on the electrical properties and supported by the surface morphologies and optical properties which have strong correlation. There are four deposition method have been focused in this study which are the immerse time, Si02 thickness, annealing temperature and the precursor solution concentration. The results have been characterized using scanning electron microscope (SEM) for the structural properties, X-ray diffractometer (XRD) for the growth orientation and IV measurement system for the electrical properties. The optical properties have been characterized using photoluminescence and UV -VIS spectrometer. Immerse time at 3 hours shows optimum electrical IV response. The Si02 thickness when oxidized at 5 minutes has optimum structural, clectrical and optical propcl1ics. Annealing thc sample at 500°C has the optimum IV response but for the optical properties, the best annealing temperature is at 550°C. The precursor solution concentration at 0.0001 M has optimum IV response but for the optimum optical properties, 0.01 M has the best response. At the end of this study, the optimized deposition parameters in sol-gel method to deposit nanostrLlctured ZnO has been obtained. The result will be a contribution for the next researcher to study other parameters using sol-gel method.